Pengenalan dan Pelatihan Autocad Untuk Meningkatkan Kompetensi Siswa SMK N 3 Semarang - Mentari Septanya Sitorus; Talitha Zhafira; Ahmad Hakim Bintang Kuncoro (Jurnal Pengabdian Masyarakat Nusantara, 2023)
One of the sciences, technologies and arts that is in line with the demands of the times and demands in the industrial world, is technical drawing using the AutoCAD program. Based on the specific objectives of Vocational Secondary Education (SMK) according to Law No. 20 of 2003 it is necessary to carry out AutoCAD training for vocational school students.. The methods used in this community service are teaching and practice methods. The result of community service is that partners gain a level of understanding in AutoCAD theory as well as the use of AutoCAD applications in building structures. This can be seen from the results of the pre-test and post-test with the value from 35% to 65% after the introduction and training of AutoCAD.